Exploring Muslim Tourist Intention on Shariah Tourism to Madura - Elfira Maya Adiba; Nasrulloh Nasrulloh (Universitas Muhammadiyah Malang, 2021)
Halal industry has experienced an increase in its supporter. Moreover, halal products have also become more preferable due to the guarantee of hygiene and safety in their usage. Halal products do not only consist of finance but also include halal food, halal cosmetic, shariah tourism, or also known as halal tourism, etc. The purpose of this research is to discover the factors that can influence Muslim tourists’ intention of traveling for shariah tourism. Primary data of this research were collected through questionnaires on 98 respondents. Thereafter, the collected data were analysed using SEM-PLS. The result found there are six factors that influence the intention of Muslim tourist to travel for shariah tourism at Madura Island, which are: personal societal perception, religious belief, infrastructure, halal marketing, halal awareness, and destination image, respectively. The personal societal perception factor was found to be the most dominant of Muslim tourist to travel.